Analisis Efektivitas Program MBKM dari Perspektif Mahasiswa: Peran dan Keterlibatan Organisasi Pendidikan (Studi Kasus pada Mahasiswa Departemen Biologi Universitas Negeri Padang) - Rahmadhani Fitri; Nurhizrah Gistituati; Rusdinal Rusdinal (Institut Agama Islam Negeri Kerinci, 2024)
Organizational development in education is a systematic approach aimed at improving the effectiveness, efficiency, and adaptability of educational institutions. In this context, the role of educational leaders is crucial in fostering a culture of collaboration and innovation. The implementation of the Merdeka Belajar-Kampus Merdeka (MBKM) program in higher education is a transformational initiative that provides flexibility in the learning process and aligns education with the needs of industry and society. This study evaluates the implementation of the MBKM program in the Biology Department of Universitas Negeri Padang from the students' perspective. Using the CIPP evaluation model (Context, Input, Process, and Product), this research collected data from 82 students who participated in MBKM activities. The analysis results indicate that teaching assistance activities are the most favored. The MBKM program is rated effective with an average evaluation of 83.20%, signifying that the program successfully enhances students' additional competencies and skills. The evaluation also shows that the MBKM program has improved students' adaptability to technological changes, 21st-century skills, and readiness for the workforce. Overall, the implementation of MBKM at UNP has positively impacted the organizational development of education, strengthening internal capacities, and enhancing the quality of higher education. Institutions need to continue optimizing the management of information and documentation related to the MBKM program to ensure better implementation in the future.